A Quest for a Theory and Practice of Authentic Assessment: An Arts-Based Approach (LEARNing Landscapes, 2008)
Multiple intelligences and learning style theories articulate that there is a diverse population of students who learn and understand in a variety of ways. If assessment is meant to be authentic and just, teachers and school systems must expand their forms of assessment not only to accommodate, but also to encourage and celebrate multiple ways of knowing. This paper provides concrete examples of how arts-based assignments can be an authentic and rigorous form of assessment.
Keywords: authentic asessment; arts-based; multiple intelligence; learning style theory